Research on the Path of Standardization Promoting the International Operation and Management of Service Trade Enterprises (Journal of Global Humanities and Social Sciences, 2025)
Currently, as a special new form of foreign trade, service trade has led to growing attention on the international operation and management of service trade enterprises amid the development of China's service trade. How to narrow the trade deficit, promote service trade exports, and explore how service trade enterprises can enhance their competitiveness in the process of international operation and management have become current research hotspots. Based on the theory of enterprise international operation and management, this paper analyzes the mechanism by which standardization promotes the development of international operation and management of service trade enterprises. Through the analysis of this mechanism, three main paths are proposed: the standardization certification path for service trade enterprises, which enhances their competitiveness in international operation and management; the standardization path for service trade enterprises, which improves the operational efficiency of their international operation and management; and the standardization-driven innovation path for service trade enterprises, which addresses internal obstacles and challenges through institutional and technological innovation, with "dual-drive" standardization facilitating service trade enterprises to achieve international operation and management.